Edukasi Mengenai Fakta - Mitos Makanan Dan Minuman Pada Atlet Basket Remaja - Ichsania, Nurul (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service program aimed to enhance nutrition literacy and critical thinking skills among adolescent basketball athletes regarding various circulating claims about food and beverages, particularly in distinguishing between factual information and myths in sports nutrition. The primary issue identified was the high prevalence of misleading information influencing young athletes, especially regarding the consumption of specific foods or drinks that are claimed to boost performance but may, in fact, impair physical condition or lead to nutritional imbalance. The program involved 25 adolescent basketball athletes and employed a Community-Based Research (CBR) approach, a participatory research model that positions the community as active agents in identifying problems and formulating solutions. The implementation consisted of four core sessions: identification of common nutrition myths through group discussions, delivery of evidence-based educational materials, myth clarification using case studies, and evaluation of participants’ understanding. The results demonstrated a significant improvement in the participants’ ability to differentiate between accurate and misleading nutrition information. Based on the final evaluation, 84% of the participants were able to explain at least three common nutrition myths along with their scientific clarification. This program provides evidence that the CBR approach is effective in fostering critical awareness and evidence-based thinking habits among young athletes.